Environmental Awareness-Based Education at English Corner Community in Sidetapa Village - Kadek Arlinda Devi Suyanti; I Wayan Putra Yasa; I Gusti Made Arya Suta Wirawan (Universitas Pendidikan Ganesha, 2023)
This study aims to explain the implementation of an environmental awareness-based education model for children in the English Corner Community in Sidetapa Village. This study uses a qualitative approach, with data collection techniques through purposive sampling, field observations, in-depth interviews, and document studies. To develop the validity of the data obtained by the researchers using the triangulation method, namely by combining various data collection techniques and existing sources. This study indicates that environmental awareness education provided by English Corner Community volunteers is given on the sidelines of the English course, starting with guiding children about the importance of protecting the environment. Collection of plastic waste around Sidetapa Village and using the environment as an object of learning media by linking objects in the environment translated into English. Thus, children at English Corner Community have the personality to care about the cleanliness of the environment.